2002
DOI: 10.1046/j.1365-2141.2002.03437.x
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of action of recombinant activated factor VII administered to patients with severe thrombocytopenia and life‐threatening haemorrhage: focus on prothrombin activation

Abstract: Summary. We report the ex vivo effect of recombinant activated factor VII (rFVIIa) on prothrombin activation after whole blood clotting. Two patients with severe thrombocytopenia and life-threatening haemorrhage were successfully managed using a single dose of rFVIIa (90 lg/kg). Western blotting using antiprothrombin antibody showed that rFVIIa did not induce thrombin generation in citrated platelet-poor plasma. Patient sera showed significantly impaired prothrombin activation before and after rFVIIa administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…The need for antidote or for a rapid and safe haemostatic method is more urgent in the case of fondaparinux, which is actually being introduced in the daily clinical practice. An attractive alternative could be the use of rFVIIa (Novoseven®), which has been show to be an effective and safe haemostatic agent in a variety of clinical conditions without inducing increased thrombin generation [28]. Recent in vitro experiments from our group showed that rFVIIa does not modify the inhibition of the endogenous thrombin potential induced by therapeutic concentrations of fondaparinux, but it significantly accelerates the generation of thrombin [11].…”
Section: Antidotementioning
confidence: 99%
“…The need for antidote or for a rapid and safe haemostatic method is more urgent in the case of fondaparinux, which is actually being introduced in the daily clinical practice. An attractive alternative could be the use of rFVIIa (Novoseven®), which has been show to be an effective and safe haemostatic agent in a variety of clinical conditions without inducing increased thrombin generation [28]. Recent in vitro experiments from our group showed that rFVIIa does not modify the inhibition of the endogenous thrombin potential induced by therapeutic concentrations of fondaparinux, but it significantly accelerates the generation of thrombin [11].…”
Section: Antidotementioning
confidence: 99%
“…Non-specific hemostatic agents such as FEIBA, prothrombin complex concentrate and rFVIIa have been considered for life-threatening bleeding. rFVIIa (Novoseven®) has been shown to be an effective and safe hemostatic agent in a variety of clinical conditions without inducing increased thrombin generation [127][128][129]. Recent in vitro experiments and ex vivo observations in healthy volunteers showed that rFVIIa does not modify the inhibition of the endogenous thrombin potential induced by therapeutic concentrations of fondaparinux in human plasma, but it significantly accelerates the generation of thrombin [130,131].…”
Section: Antidote For the New Antithrombotic Agentsmentioning
confidence: 99%
“…Flow-cytometric analysis revealed CD33, CD34 and HLA DR positivity of the blasts, and acute myeloid leukemia M0 (by FrenchAmerican-British classification) was diagnosed. The MITUS regimen consisting of daunorubicin 45 mg/m 2 [1][2][3], cytarabine (ARA-C) 100 mg/m 2 [1][2][3][4][5][6][7], high-dose cytarabine (HIDAC) 2 g/m 2 [8][9][10] was given.…”
Section: Case Reportmentioning
confidence: 99%
“…It can activate factor X to activated factor X (FXa), as well as factor IX to activated factor IX. FXa, in complex with other factors, then converts prothrombin to thrombin, which leads to the formation of a hemostatic plug by converting fibrinogen to fibrin and thereby inducing local hemostasis [2]. rFVIIa has additionally been considered a universal haemostatic agent, prompting its use in the management of severe uncontrolled surgical bleeding in patients without pre-existing coagulopathies [3].…”
Section: Introductionmentioning
confidence: 99%